Patterns of motivation towards innovative online learning amongst agricultural undergraduates - Asmuni, Azizan; Arif Shah, Jasmin; Hashemyolia, Shayesteh (University Community Transformation Centre, Universiti Putra Malaysia, 2017)
Online learning has become an effective supplementary mode of knowledge delivery. Information and Communication Technology (ICT) competency for agriculture graduates are important to enhance their extension roles in agricultural and rural development. Thus agriculture students should be motivated towards use of ICT especially in online learning as it could facilitate a more engaged learning since the students could learn at their own pace according to individual varying learning needs. Amongst others, online learning provides access to courses, communication and collaborative assignment. However effectiveness of online learning to a certain extent is dependent on students’ motivation to adopt its use. Thus, this study was undertaken to determine students’ levels of motivation in online learning by applying the Motivated Strategies for Learning Questionnaire. The study involved 78 undergraduate students from the Faculty of Agriculture of Universiti Putra Malaysia. The reliability of scale was measured by internal consistency analyses whilst students’ levels of motivation in online learning detected by descriptive analyses. A survey method was used to elicit answers to research questions. The findings show that the level of agricultural students’ motivation in online learning stands at moderate level. Online mode of learning has effectively complemented traditional classroom method for agriculture undergraduates at Universiti Putra Malaysia.